Advances in Nonlinear Speech Processing 6th International Conference, NOLISP 2013, Mons, Belgium, June 19-21, 2013. Proceedings - Drugman, Thomas; Dutoit, Thierry; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 6th International Conference on Nonlinear Speech Processing, NOLISP 2013, held in Mons, Belgium, in June 2013. The 27 refereed papers included in this volume were carefully reviewed and selected from 34 submissions. The paper are organized in topical sections on speech and audio analysis; speech synthesis; speech-based biomedical applications; automatic speech recognition; and speech enhancement.
Speech and Audio Analysis -- Evaluation of Automatic Glottal Source Analysis -- NMF-Based Spectral Analysis for Acoustic Event Classification Tasks -- Efficient GCI Detection for Efficient Sparse Linear Prediction -- Gender Detection in Running Speech from Glottal and Vocal Tract Correlates -- An Efficient Method for Fundamental Frequency Determination of Noisy Speech -- Glottal Source Model Selection for Stationary Singing-Voice by Low-Band Envelope Matching -- Contribution to the Multipitch Estimation by Multi-scale Product Analysis -- Speech Signals Parameterization Based on Auditory Filter Modeling -- Towards a Better Representation of the Envelope Modulation of Aspiration Noise -- Speech Synthesis -- Towards Physically Interpretable Parametric Voice Conversion Functions -- Reduced Search Space Frame Alignment Based on Kullback-Leibler Divergence for Voice Conversion -- Average Voice Modeling Based on Unbiased Decision Trees -- Non-linear Pitch Modification in Voice Conversion Using Artificial Neural Networks -- Speech-Based Biomedical Applications -- Analysis and Quantification of Acoustic Artefacts in Tracheoesophageal Speech -- Analysis of Speech from People with Parkinson$1 (Bs Disease through Nonlinear Dynamics -- Synthesis by Rule of Disordered Voices -- Towards a Low-Complex Breathing Monitoring System Based on Acoustic Signals -- Automatic Detection of Laryngeal Pathologies in Running Speech Based on the HMM Transformation of the Nonlinear Dynamics -- Feature Extraction Approach Based on Fractal Dimension for Spontaneous Speech Modelling Oriented to Alzheimer Disease Diagnosis -- Automatic Speech Recognition -- Robust Hierarchical and Sparse Representation of Natural Sounds in High-Dimensional Space -- On the Importance of Pre-emphasis and Window Shape in Phase-Based Speech Recognition -- Smoothed Nonlinear Energy Operator-Based Amplitude Modulation Features for Robust Speech Recognition -- Fuzzy Phonetic Decoding Method in a Phoneme Recognition Problem -- Improved EMD Usable Speech Detection for Co-channel Speaker Identification -- Speech Enhancement -- Speech Enhancement: A Multivariate Empirical Mode Decomposition Approach -- Speech Denoising Based on Empirical Mode Decomposition and Improved Thresholding -- A Fast Semi-blind Reverberation Time Estimation Using Non-linear Least Squares Method.s
Keywords: Computer science; Artificial intelligence; Translators (Computer programs).; Optical pattern recognition; Computer Science; Pattern Recognition; Artificial Intelligence (incl. Robotics).; Language Translation and Linguistics; Computer Science, general; Computer Science, general